Development and validation of a crisis self‐efficacy index. (6th January 2019) - Park, Sejin; Avery, Elizabeth Johnson
Abstract: This study develops a crisis self‐efficacy index to provide a tool for crisis communication researchers and practitioners to understand behavioural aspects of crisis response better. Evaluations of public's crisis self‐efficacy using this index inform strategic message development to protect the public and minimize crisis damages by identifying the public/s most in need of self‐efficacy enhancing interventions. The index also provides practitioners a useful longitudinal index to evaluate progress in crisis preparedness programs and track changes in efficacy. A four‐stage survey index development process using structural equation modelling identifies four underlying constructs of crisis self‐efficacy: action, preventive, achievement and uncertainty management.